"They Just Don't Stand for Nothing": LGBT Christians' Definitions of Non-Religious Others. (8th August 2016) - Sumerau, J. E.
In this exploratory study, I examine how a group of LGBT Christians conceptualized non-religious others. Based on over 450 hours of fieldwork in an LGBT Christian church located in the southeastern region of the United States, I demonstrate how a group of LGBT Christians defined non-religious others as (1) morally suspect and untrustworthy, (2) in need of salvation and guidance, and (3) poor representations of the LGBT community. Although these LGBT Christians used "non-religious" as a catchall term without ever specifying exactly who it captured, they used the first two definitions to apply to non-religious people in general regardless of sexuality while explicitly focusing on non-religious sexual minorities in their third definition. Moreover, I show how these definitions echoed mainstream religious rhetoric in America used to marginalize both sexual and religious minorities. In conclusion, I draw out two central implications of this work: (1) how religious depictions of non-religious people may reproduce societal patterns of inequality; and (2) the importance of analyzing how religious people define and interpret non-religious others.